An Investigation of Tone Perception and Production in German Learners of Mandarin - DING, Hongwei; HOFFMANN, Rudiger; JOKISCH, Oliver (Archives of Acoustics, 2011)
This study investigates the possible errors related to Mandarin tone perceptionand production by German speakers. In a preliminary test, 23 German listenersshould identify the tones of 186 monosyllables. Results show that exposure to Man-darin Chinese can help to discriminate lexical tones as highly expected. In the mainexperiment, 17 German subjects were asked to take part in a perception and pro-duction test. Stimulus of perception involves 48 monosyllables uttered by a standardprofessional Chinese speaker; acoustic measures were conducted to analyze the pro-duction of 72 monosyllables for each subject. It is found that German speakershave much smaller f0 range than Chinese native speakers. Findings can provideimplications for cross language studies and teaching practices.